Pengembangan Sistem Pemesanan Jasa Fotografi dengan Integrasi Payment Gateway Berbasis Android - Ardabili, Muhammad Yusuf; Fachrie, Muhammad (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Vibesroom Photography is a business that provides documentation services for various types of events, such as applications, weddings, graduations, and others. However, the transaction process used is quite complicated, causing several problems, such as difficulties in carrying out transactions, managing transaction data, and scheduling. The goal of this research is to develop a system that can assist Vibesroom Fotografi in conducting transaction processes, managing data, and integrating with Midtrans as a payment gateway. In the process of developing a photography services ordering system, the waterfall method is applied because it can ensure that system development runs systematically and in a planned manner. This system development uses the Dart programming language and Flutter framework. The system is tested using the black box testing method, which is oriented towards testing system functionality. The test results show 100% valid testing, which means the system can run well. Therefore, it is expected that this system will enhance the convenience of transactions, data management, and scheduling at Vibesroom Fotografi.